2002
DOI: 10.1007/s00784-001-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of third molar impaction in a group of volunteers in Turkey

Abstract: The aim of this study was to investigate the different variables in mesio-vertically positioned impacted or erupted third molars in a group of volunteers in Turkey to determine the angular changes and levels of eruption radiographically using standardised panoramic radiographs. There were 213 volunteers with impacted and erupted third molars included in this study, most of whom were dental students. Standardised panoramic radiographs were taken from all the volunteers. The radiographic parameters included angu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
4
15
2
2
Order By: Relevance
“…[6][7][8][9][10][11][12][13] Our results indicate that retromolar space and space/width ratio were significantly larger in the subgroup of erupted mandibular third molars (P , .001). Furthermore, significantly larger sizes of retromolar space and space/width ratio were observed in the adult rather than in the early adult subgroup of patients (P , .001).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13] Our results indicate that retromolar space and space/width ratio were significantly larger in the subgroup of erupted mandibular third molars (P , .001). Furthermore, significantly larger sizes of retromolar space and space/width ratio were observed in the adult rather than in the early adult subgroup of patients (P , .001).…”
Section: Discussionmentioning
confidence: 54%
“…During the past decades, extensive research has been conducted in this field because of the high rate of third molar impaction and controversial results regarding potential predictors. [6][7][8][9][10][11][12][13] The lower third molar eruption is a complex process that depends on several factors. For a long time, insufficient development of retromolar space has been considered to be the most important factor contributing to the high impaction rate of lower third molars.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, retromolar space/third molar crown width ratio was significantly smaller in the impacted group. 30 The protocol study has not taken into account the sexual dimorphism because the third molars behave differently to the other teeth; mature and erupt earlier in female subjects. Some authors concluded that the right and left mandibular molars have the same pattern of development and emergence and over the age of 18, no relevant differences were observed between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in this study, mesial inclination of the mandibular third molar and distal inclination of the maxillary third molar were found to be indicative of the tendency for these teeth to be impacted. Mollaoglu et al [18] reported that individuals with mesioangular tooth inclination had insufficient space in the retromolar region.…”
Section: Discussionmentioning
confidence: 99%